Peran Nilai Islami Anggota Koperasi dalam Meningkatkan Eksistensi Lembaga - Witri Retno Handayani; Umrotul Khasanah (IQTISHODUNA, 2021)
The role of Islamic values in an institution properly and correctly will influence people's decisions to become members of the institution. This study aims to analyze the role and implications of Islamic values of the members of the KSU SWM Malang city, in improving the existence of the institution. The method used is descriptive qualitative research methods. Data collection techniques with in-depth interviews, observation and documentation. The informants in this study were several traders of the Dinoyo traditional market in Malang city, the chairman of the SWM cooperative management and the manager of the SWM cooperative. The results of the study found that the Islamic value of the members of the SWM cooperative was shown in the form of solidarity / teamwork, sincerity and trust in the good performance of the management, as well as the KSU-SWM manager.